Wdrażanie metod zarządzania jakością przez dostawców oprogramowania i odbiorców: Implementing methods of quality management by suppliers of the software and recipients - Skroban, Katarzyna (Management and Administration Journal, 2021)
The area in this paper is associated with using tools of improving the quality for the improvement in functioning of IT enterprises and tools which can be used by users-recipients of the software. Briefly characterized were tools which in the assessment of the author, can be used in the IT industry. An analysis was made on the possibility of the application of tools in individual phases of the life cycle of the software, particularly from the point of view of the supplier and the recipient. Also mentioned were specific methods applied for assuring qualities in computer enterprises.